2017
DOI: 10.1093/intimm/dxx002
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived extracellular vesicles: a glimmer of hope in treating Alzheimer’s disease

Abstract: One of the pathological hallmarks of Alzheimer's disease (AD) is the presence of extracellular plaques resulting from the accumulation of beta-amyloid peptide (Aβ). To date, a definitive cure for this disease is still lacking as the currently approved drugs used are mainly symptomatic treatments. The revolutionary discovery of extracellular vesicles (EVs) has shed new light on the development of disease-modifying treatments for AD, owing to their potential in delivering the therapeutic agents to the brain. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 112 publications
0
51
0
1
Order By: Relevance
“…Extensive investigations have shown that MSCs can cross the blood-brain barrier via intracerebral (transplantation into hippocampus or lateral ventricles), intracarotid, or intravenous injections (Lo Furno et al, 2017 ). These cells and their extracellular vesicles could stimulate neurogenesis (Oh et al, 2015 ) and could significantly rescue learning and memory deficits of animals with Aβ deposition reduction and modification of size and number of microglial cells (Duncan and Valenzuela, 2017 ; Liew et al, 2017 ). However, MSCs have a low survival rate after transplanted due to the adverse microenvironment [i.e., presence of cytotoxic Aβ oligomers and p-tau, and increased reactive oxygen species (ROS)] (Lee et al, 2015 ; Oh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have shown that MSCs can cross the blood-brain barrier via intracerebral (transplantation into hippocampus or lateral ventricles), intracarotid, or intravenous injections (Lo Furno et al, 2017 ). These cells and their extracellular vesicles could stimulate neurogenesis (Oh et al, 2015 ) and could significantly rescue learning and memory deficits of animals with Aβ deposition reduction and modification of size and number of microglial cells (Duncan and Valenzuela, 2017 ; Liew et al, 2017 ). However, MSCs have a low survival rate after transplanted due to the adverse microenvironment [i.e., presence of cytotoxic Aβ oligomers and p-tau, and increased reactive oxygen species (ROS)] (Lee et al, 2015 ; Oh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant research is still required in order to guarantee the long-term biological safety of these exosomes, and confirm the potential adverse effects and efficacy of exosome administration in patients with AD. 114 We also need to know more about the time of administration, the most effective route of administration, including dose-response experiments, before considering MSC-derived exosomes for clinical application.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…The exosomes and microvesicles released from modified MSCs are enriched in factors of interest to enhance the therapeutic effects. Overexpression of Aβ degrading enzymes or downregulation of secretase enzymes related to Aβ formation with transfecting different RNAs can be useful in ameliorating disease symptoms (153). Brn-4 protein in MSCs can inhibit the accumulation of Aβ in the brain but miR-937 presence impedes the translation of Brn-4 mRNA to protein.…”
Section: Alzheimer's Diseasementioning
confidence: 99%